Partisipasi Orang Tua Murid dalam Meningkatkan Kualitas Pendidikan MI Assa’adah Labuapi Kabupaten Lombok Barat Provinsi Nusa Tenggara Barat - Mastur (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2020)
This study aims to determine; 1). How parents' participation in improving the quality of Education in MI Assa'adah Labuapi, West Lombok Regency 2019-2020 Academic Year, 2). Want to know what obstacles are faced in improving the quality of Education in MI Assa'adah Labuapi, West Lombok Regency, Academic Year 2019-2020. Data collection methods that the authors use in this study are, the Observation Method (observation), Interview Method (Interview), and the Documentation Method. MI Assa'adah Labuapi, West Lombok, is considered quite successful in making people aware of the importance of participating in carrying out the education of their children, from the research results obtained 1). Parental participation such as helping to improve madrasas, whether in the form of assistance with energy, money or other building materials, besides that parents also help children learn at home by meeting the needs of their children and guiding learning, 2). The obstacle faced by MI Assa'adah Labuapi West Lombok is the number of teachers that are not balanced with the number of students because there is only one teacher from the country besides honorary teachers, inadequate facilities and infrastructure such as benches, some is slightly damaged and the condition of the room has not been well organized. and the hall is still joined by other institutions.